Effect of melatonin treatment on 24-h variations in responses to mitogens and lymphocyte subset populations in rat submaxillary lymph nodes - Castrillon, P. O. (2000)
Wistar male rats were injected s.c. with melatonin (30 μg) or vehicle, 1 h before lights off, for 11 days. Ten days after beginning melatonin treatment, rats received Freund's complete adjuvant or its vehicle s.c., and after 2 days, they were sacrificed at six different time intervals throughout a 24-h cycle. The mitogenic effect of lipopolysaccharide (LPS) and concanavalin A (Con A), the activity of ornithine decarboxylase (ODC) and the relative size of lymphocyte subset populations were measured in submaxillary lymph nodes. In control rats, the mitogenic effects of LPS and Con A and ODC activity peaked during the afternoon. Injection of Freund's adjuvant induced a 10-h shift in the diurnal rhythm of the mitogenic effect of LPS to attain maximal values at night. Melatonin pretreatment blunted the daily variations in the mitogenic activity of Con A or LPS and, when given to Freund's adjuvant-injected rats, augmented mesor and amplitude of diurnal rhythm in ODC activity. Maxima in B cell number occurred at night whereas those of T and B-T cell number occurred during the afternoon. During the early phase of immunization tested, the number of B cells augmented and the amplitude of its diurnal rhythmicity increased both after immunization and following melatonin pretreatment. Maxima of 24-h rhythms in CD4+ and CD4+/CD8+ cell populations occurred during the afternoon while those of CD8+ cells occurred at late night. Melatonin significantly augmented CD4+ cell number and decreased CD8+ cell number; it therefore augmented the CD4+ :CD8+ ratio. The results suggest that pretreatment with a pharmacological dose of melatonin exerts immunomodulating effects at an early, preclinical, phase of Freund's adjuvant-induced arthritis in rats.